2019
DOI: 10.3390/ijms20133160
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Alleviates Thiram-Induced Tibial Dyschondroplasia by Modulating Caspases, BECN1 Expression and ECM Degradation

Abstract: Chlorogenic acid (CGA) is a widely applied traditional Chinese medicine ingredient which can be used for the treatment of osteoporosis. In this experiment, we investigated the potential therapeutic effect of chlorogenic acid on thiram-induced tibial dyschondroplasia (TD) and explored the underlying mechanisms that have been rarely mentioned by others yet. Performance indicator analysis and tibial parameter analysis showed that CGA exhibited a definite positive effect on thiram-induced TD chickens. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
5
16
0
Order By: Relevance
“…Moreover, chondrocytes with intact nuclei were much greater in PTE bones than the TD bones as in agreement with other studies [43,45,47]. Chicks with TD exhibited scattered dead and anucleate cells, opaque cartilage, abnormal arrangement of bone cells with disintegrated and dissolved nuclei and a higher percentage of extracellular matrix as in accordance with other researchers [43,44]. This is due to the fact that avascularization in tibia, non-calcification, and increased extracellular matrix lead to a decline in angiogenesis that disturbs the nutrient transportation to developing chondrocytes [9,47].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, chondrocytes with intact nuclei were much greater in PTE bones than the TD bones as in agreement with other studies [43,45,47]. Chicks with TD exhibited scattered dead and anucleate cells, opaque cartilage, abnormal arrangement of bone cells with disintegrated and dissolved nuclei and a higher percentage of extracellular matrix as in accordance with other researchers [43,44]. This is due to the fact that avascularization in tibia, non-calcification, and increased extracellular matrix lead to a decline in angiogenesis that disturbs the nutrient transportation to developing chondrocytes [9,47].…”
Section: Discussionsupporting
confidence: 93%
“…The PTE administration alleviated the adverse effects of thiram, and increased the angiogenesis which restored the chondrocytes' arrangement, the network of blood vessels and bone trabecular ratio. Moreover, chondrocytes with intact nuclei were much greater in PTE bones than the TD bones as in agreement with other studies [43,45,47]. Chicks with TD exhibited scattered dead and anucleate cells, opaque cartilage, abnormal arrangement of bone cells with disintegrated and dissolved nuclei and a higher percentage of extracellular matrix as in accordance with other researchers [43,44].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Tibial Dyschondroplasia (TD) is a severe bone metabolic disorder that adversely affects the proximal growth plate (GP) of the tibia and usually occurs in fast growing chicks (Nabi et al, 2016a(Nabi et al, , 2016b. Present study revealed that chicks fed with thiram-feed exhibited higher TD score and GP measurement with tibial inflammation and inability to walk properly as compared to healthy chicks which leads to reduced growth rate, weight gain and liver weight and increased mortality as reported formerly (Zhang et al, 2019). Treatment with GSE remarkably reduced the TD score and inflammation along with diminishing lesions from the GP region.…”
Section: Discussionsupporting
confidence: 48%